Perception of Ecotourism among Tertiary Institution Students in Abeokuta Metropolis, Ogun State, Nigeria (2018)
The study determined tertiary students’ perception of ecotourism in Abeokuta, Ogun State. Data was garnered from 405 students who were randomly sampled from six tertiary institutions namely; Federal University of Abeokuta (94), Crescent University (23), Federal College of Education Osiele (80), Moshood Abiola Polytechnic Ojere (145), Sacred Heart School of Nursing Lantoro (31) and School of Nursing FMC Idi-Aba (32). The results of this study was presented using descriptive statistical tools such as frequencies, percentages and means, while inferential statistical tool used was Chi Square. The modal age category was 21-25 years (55.1%). Most of the students were female (60.5%) and single (96.8%). The percentages of students in 100 (36.0%) and 200 (32.1%) level were more compared to other levels of study. Students who were aware of ecotourism got to know about it mostly through school (15.6%) and personal interest (11.9%). Only 17.0% indicated awareness of ecotourism initiatives, club or society in their schools, while only 8.6% of the students had ever participated in ecotourism activities.The few students who participated in ecotourism activities engaged in rock climbing (3.2%), sightseeing (1.7%), visitation (1.2%) and trekking (1.5%) once in a while (4.9%). Some (33.6%) of the students indicated lack of information and time (14.8%) as constraining their participation in ecotourism activities. Almost all (90.9%) respondents reflected that they would like to know more about ecotourism. The main reason that stimulates students’ interest in ecotourism was to understand the natural environment (46.9%) and get close to nature (20.7%). Most of the students were favorably disposed towards ecotourism bringing about infrastructural development ( =4.20), positive changes in value system of the community ( =4.30) and employment opportunity for indigenous population ( =4.41). Significant relationship existed between institution attended (χ2 = 0.274, p<0.01), level of study (χ2 = 0.174, p<0.05) and perception of ecotourism. The study recommends intensification of ecotourism awareness, ecotourism advocacy and promotion of programmes that will encourage students’ participation in ecotourism activities.